Leiopathes glaberrima millennial forest from SW Sardinia as nursery ground for the small spotted catshark Scyliorhinus canicula. Issue 3 (29th December 2016) - Cau, Alessandro; Follesa, Maria Cristina; Moccia, Davide; Bellodi, Andrea; Mulas, Antonello; Bo, Marzia; Canese, Simonepietro; Angiolillo, Michela; Cannas, Rita
Abstract: Association between habitat structuring organisms and other species has great relevance for ecosystem‐based conservation measures. Those occurring in temperate areas, particularly in the upper portion of the continental margin, are mostly unknown or not properly understood because of the difficulty to discriminate co‐occurrence and real functional linkages among species. Deep water coral assemblages over the Carloforte Shoal (south‐west Sardinia; 180–210 m depth) were investigated using ROV surveys. During the surveys, more than 740 egg‐capsules of the spotted catshark Scyliorhinus canicula, identified after hatching experiments in captivity, were found attached exclusively to colonies of the long‐living black coral Leiopathes glaberrima . Although based on a spot finding, the results show that coral forests are not only hotspots of biodiversity, but can also serve as nursery grounds for S. canicula . The protection of these millennial coral forests is therefore to be considered a priority.